Evaluation of multiple plastic recycling in Benghazi-Libya - A. Elsheikhi, Salah; A. Mohamed, Hamzah; A. Eldressi, Khaled (Libyan Journal of Science &Technology, 2022)
This study is aimed at evaluating how feasible is the production of moulded products based on multiple recycled materials in order to manufacture new products without compromising the product quality. The effect of the reprocessing on the properties (mass, shrinkage, density, and colour) was examined. It has been reported that no significant change in these properties occurred.